Effectiveness and Safety of Atazanavir Use for the Treatment of Children and Adolescents Living With HIV: A Systematic Review - Saint-Lary, Laura; Dassi Tchoupa Revegue, Marc Harris; Jesson, Julie; Renaud, Françoise; Penazzato, Martina; Townsend, Claire L.; O'Rourke, John; Leroy, Valériane; , WHO HIV Hepatitis and STIs (HHS) Department (Frontiers in Pediatrics, 2022)
Background: Atazanavir/ritonavir is recommended as a preferred second-line antiretroviral regimen in children older than three months, alternatively to lopinavir/ritonavir. We performed a systematic review to assess safety and effectiveness of atazanavir use in children and adolescents. Methods: We searched observational studies and clinical trials on Web of Science, Embase and Cochrane CENTRAL database between 2009/01/01 and 2020/10/01; as well as grey literature. We extracted safety (adverse events, grade 3 or 4 adverse events, treatment discontinuation) and effectiveness (CD4 cell counts and HIV viral load) outcomes. We estimated weighted summary pooled incidence with corresponding 95% confidence intervals. Results: Out of the 1085 records screened, we included five studies (one comparative cohort, three single phase 2-3 trial arms, one retrospective cohort) reporting 975 children and adolescents, of whom 56% (544) received atazanavir. Three studies reported all-cause treatment discontinuation rates, yielding a pooled incidence of 19% [15-22] at 12 months. The comparative cohort compared atazanavir to darunavir, with few grade 3-4 adverse events, except transient hyperbilirubinemia, occurring in half (92/188) of the atazanavir patients. No death occurred (two studies reporting). Four studies described increased CD4 cell counts and decreased HIV viral load at 6 or 12 months. Conclusion: Few safety and effectiveness data were available for children and adolescents exposed to atazanavir. Transient grade 3-4 hyperbilirubinemia was the main adverse outcome reported. Immune and viral responses were descriptive. The use of atazanavir/ritonavir in children and adolescents needs further investigation, but remains a suitable option for a preferred second-line antiretroviral regimen. PROSPERO number: CRD42022309230